EVALUATION OF PLANT GROWTH PROMOTING RHIZOBACTERIA IN WHEAT FOR MANAGEMENT OF SPOT BLOTCH DISEASE (Journal of Plant Disease Sciences, 2017)
Effect of seven different plant growth promoting rhizobacteria (PGPR) on growth promotion of wheat cultivars well as their influence on development of spot blotch disease were evaluated. Maximum enhancement of growth, dry biomass and grain yield was observed in wheat plants treated with Bacillus megatarium Bacillus methylotrophicus (NAIMCC-B-01954) followed by (NAIMCC-B-01492) and (NAIMCC-B-01484). Activities of Bacillus altitudinis defense enzymes . peroxidase, chitinase, glucanase and PAL were evaluated in viz treated and untreated wheat plants following artificial inoculation with Bipolaris sorokiniana confirming induction of disease resistance. PGPR treatment also reduced the percentage disease index from 84.2% in untreated inoculated plants to 9.6% in treated inoculated plants. It was hence confirmed that application of PGPR can enhance the growth and disease resistance in wheat cultivars.
Keywords: PGPR, wheat, growth promotion, disease resistance